Independent component analysis of resting state activity in pediatric obsessive‐compulsive disorder. Issue 10 (28th May 2014) - Gruner, Patricia; Vo, An; Argyelan, Miklos; Ikuta, Toshikazu; Degnan, Andrew J.; John, Majnu; Peters, Bart D.; Malhotra, Anil K.; Uluğ, Aziz M.; Szeszko, Philip R.
Abstract Obsessive‐compulsive disorder (OCD) is an often severely disabling illness with onset generally in childhood or adolescence. Little is known, however, regarding the pattern of brain resting state activity in OCD early in the course of illness. We therefore examined differences in brain resting state activity in patients with pediatric OCD compared with healthy volunteers and their clinical correlates. Twenty‐three pediatric OCD patients and 23 healthy volunteers (age range 9–17), matched for sex, age, handedness, and IQ completed a resting state functional magnetic resonance imaging exam at 3T. Patients completed the Children's Yale Brown Obsessive Scale. Data were decomposed into 36 functional networks using spatial group independent component analysis (ICA) and logistic regression was used to identify the components that yielded maximum group separation. Using ICA we identified three components that maximally separated the groups: a middle frontal/dorsal anterior cingulate network, an anterior/posterior cingulate network, and a visual network yielding an overall group classification of 76.1% (sensitivity = 78.3% and specificity = 73.9%). Independent component expression scores were significantly higher in patients compared with healthy volunteers in the middle frontal/dorsal anterior cingulate and the anterior/posterior cingulate networks, but lower in patients within the visual network. Higher expression scores in the anterior/posterior cingulate network correlated with greater severity of compulsions among patients. These findings implicate resting state fMRI abnormalities within the cingulate cortex and related control regions in the pathogenesis and phenomenology of OCD early in the course of the disorder and prior to extensive pharmacologic intervention. Hum Brain Mapp 35:5306–5315, 2014. © 2014 Wiley Periodicals, Inc.